Dynamic Theta Networks in the Human Medial Temporal Lobe Support Episodic Memory - Solomon, Ethan A.; Stein, Joel M.; Das, Sandhitsu; Gorniak, Richard; Sperling, Michael R.; Worrell, Gregory; Inman, Cory S.; Tan, Ryan J.; Jobst, Barbara C.; Rizzuto, Daniel S.; Kahana, Michael J. (Current biology, 2019)
The medial temporal lobe (MTL) is a locus of episodic memory in the human brain. It is comprised of cytologically distinct subregions that, in concert, give rise to successful encoding and retrieval of context-dependent memories. However, the functional connections between these subregions are poorly understood. To determine functional connectivity among MTL subregions, we had 131 subjects fitted with indwelling electrodes perform a verbal memory task and asked how encoding or retrieval correlated with inter-regional synchronization. Using phase-based measures of connectivity, we found that synchronous theta (4–8 Hz) activity underlies successful episodic memory. During encoding, we observed a dynamic pattern of connections converging on the left entorhinal cortex, beginning with the perirhinal cortex and shifting through hippocampal subfields. Retrieval-associated networks demonstrated enhanced involvement of the subiculum and CA1, reflecting a substantial reorganization of the encoding network. We posit that coherent theta activity within the MTL marks periods of successful memory, but distinct patterns of connectivity dissociate key stages of memory processing. •We assessed intra-MTL connectivity during a memory task in 131 epilepsy patients•Successful encoding and retrieval were correlated with elevated theta connectivity•Left entorhinal cortex emerged as a hub of intra-MTL connectivity•We found broad increases in high-frequency power but decreases in theta power The medial temporal lobe (MTL) is key to episodic memory, but little is known about communication between its subparts. Solomon et al. analyze phase relations between MTL subregions in 131 humans with depth electrodes, identifying the entorhinal cortex as a hub of theta connectivity during encoding, and a reorganized network supporting retrieval.